2010
DOI: 10.1016/j.yjmcc.2009.09.013
|View full text |Cite
|
Sign up to set email alerts
|

TIMPs and cardiac remodeling: ‘Embracing the MMP-independent-side of the family’

Abstract: a b s t r a c t a r t i c l e i n f oUnraveling the biological role of tissue inhibitors of metalloproteinases (TIMPs) during cardiac remodeling and the progression of heart failure has proven to be an enormous challenge. Remodeling of the cardiac extracellular matrix (ECM), regulated by matrix metalloproteinases (MMPs) and their endogenous inhibitors, TIMPs, is a well-established paradigm in cardiac health and disease. Originally, TIMPs were thought to function exclusively as endogenous inhibitors of MMP acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
103
0
3

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(113 citation statements)
references
References 65 publications
0
103
0
3
Order By: Relevance
“…Additionally, the present study demonstrates that fetal hypoxia increases TIMP-3 and TIMP-4 expression levels in both fetal and neonatal hearts, suggesting another possible mechanism in the hypoxia-mediated downregulation of myocyte proliferation. In addition to the roles in modulating MMPs, it has been demonstrated that both TIMP-3 and TIMP-4 play a key role in inhibiting cardiomyocyte proliferation in rat hearts possibly in a MMP-independent and receptor-mediated manner (13,16,17,42).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, the present study demonstrates that fetal hypoxia increases TIMP-3 and TIMP-4 expression levels in both fetal and neonatal hearts, suggesting another possible mechanism in the hypoxia-mediated downregulation of myocyte proliferation. In addition to the roles in modulating MMPs, it has been demonstrated that both TIMP-3 and TIMP-4 play a key role in inhibiting cardiomyocyte proliferation in rat hearts possibly in a MMP-independent and receptor-mediated manner (13,16,17,42).…”
Section: Discussionmentioning
confidence: 99%
“…MMPs are a family of zinc-dependent proteases that consist of at least 25 different MMPs in vertebrate (12). Although the most studied MMPs in the heart are gelatinases, MMP-2 and MMP-9, that are capable of degrading type I and IV collagens, the major types of fibrillar collagens in the heart are type I and III collagens that are digested mainly by collagenase-1 (MMP-1) and collagenase-3 (MMP-13), respectively (40,42,44). In addition to the secreted MMPs, there is a unique subfamily of MMPs, namely membrane type(MT)-MMPs.…”
mentioning
confidence: 99%
“…The composition of the ECM is regulated by enzymes, the matrix metalloproteinases (MMP), which degrade the ECM components, and their inhibitors, tissue inhibitors of MMP (TIMP-1 to -4), which indirectly lead to ECM deposition (Vanhoutte and Heymans, 2010). Matrix metalloproteinase and TIMP imbalance and ECM degradation and deposition are associated withcardiac diseases and dysfunction (Spinale, 2007), but onlylittle is known about their role in age related cardiac changes.…”
Section: Increased Ventricular Stiffness Is Caused By Imbalanced Extrmentioning
confidence: 99%
“…Enquanto o TIMP-1, -2 e -4 permanecem solúveis e difusíveis, o TIMP-3 esta ligado a ECM (Vanhoutte and Heymans 2010).…”
Section: Timpsunclassified
“…Além disso, o TIMP-1 não possui ação inibitória sobre as MT-MMPs (Kandasamy, Chow et al 2009), e o TIMP-2 não interagem com a MMP-9 (Vanhoutte and Heymans 2010 Além disso, os TIMPs possuem atividades biológicas independentes da sua ação inibitória sobre as MMPs, tais como: crescimento e diferenciação celular, migração celular, anti-angiogenese, e efeito anti-e pró-apoptótico, sendo que os receptores para tais ações ainda estão sendo investigados (Kandasamy, Chow et al 2009;Vanhoutte and Heymans 2010).…”
Section: Timpsunclassified